Peningkatan Kemampuan Komunikasi Dan Pemecahan Masalah Matematika Melalui Strategi Think Talk Write (PTK pada Siswa Kelas VIII G Semester Ganjil SMP Negeri 1 Juwiring Tahun 2015/2016) - Rahmawati, Atika (2016)
The purpose of this study is to describe the increasing of communication skills and solving mathematical problems with the subject VIIIG grade students of SMP Negeri 1 Juwiring the academic year 2015/2016 through think talk write strategy. This study is a classroom action research. The technique of collecting data through observation, testing, field notes, and documentation. Data analysis techniques include the reduction of the data, the presentation of data, and the withdrawal of the conclusion. For the validity of the data used the technique of triangulation. The results showed the increasing of communication skills: 1) write: express or reflects his thoughts in writing (poured on the paper / stationery etc.) before action 7 students (21.87%) after the action of 24 students (75%), 2) drawing: express ideas through symbols, charts, diagrams or other images, to clarify the circumstances of a problem before the act of 8 students (25.00%) after action 24 students (75.00%), 3) express of mathematical ideas through oral and demonstrate and describe it visually to obtain solving strategies problems before action 6 students (18.75%) after action 23 students (71.87%). While the increasing of mathematical problem solving can be seen from: 1) understand the problem before action of 12 students (37.50%) after action 23 students (71.87%), 2) settlement of the problem before the action plan of 10 students (31.25%) after the act of 25 students (78.12%), 3) implementing appropriate problem-solving action plan before 9 students (28.12%) after action 24 students (75.00%). Based on the description above concluded that the implementation strategy think talk write can improve communication and solving mathematical problems.